2017
DOI: 10.1007/s11255-017-1724-6
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and urinary KIM-1 relate to tumor characteristics in patients with clear renal cell carcinoma

Abstract: The objective of this prospective follow-up trial was to ascertain whether the urinary kidney injury molecule-1 (uKIM-1) associates with tumor tissue (tKIM-1) expression and with the pathological characteristics of clear renal cell carcinoma (cRCC) in radically nephrectomized (RN) and/or in partially nephrectomized (PN) patients with cRCC, pre- and postoperatively. This clinical study included 40 patients subjected to RN/PN (cRCC group) and 30 healthy volunteers (control group). Urinary KIM-1 was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
11
0
8
Order By: Relevance
“…Of note, some data also demonstrate that TIM-1 may have a novel function as part of the regulatory apparatus for tight junction of endothelial cells [28]. Moreover, increased TIM-1 expression is also found in certain human cancer tissues, such as gastric cancer, clear renal cell carcinoma, LCS, primary central nervous system lymphoma, colorectal cancer and so on, and the expression level of TIM-1 in cancer tissues or cancer cells is significantly correlated with cancer progression and survival of the patients [1921, 29, 30]. Interestingly, some data have also reported that activation of TIM-1 signaling by using TIM-4 fusion protein can lead to the cell apoptosis in colon cancer cells, suggesting a different role of TIM-1 in defining cell fate of cancer cells [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, some data also demonstrate that TIM-1 may have a novel function as part of the regulatory apparatus for tight junction of endothelial cells [28]. Moreover, increased TIM-1 expression is also found in certain human cancer tissues, such as gastric cancer, clear renal cell carcinoma, LCS, primary central nervous system lymphoma, colorectal cancer and so on, and the expression level of TIM-1 in cancer tissues or cancer cells is significantly correlated with cancer progression and survival of the patients [1921, 29, 30]. Interestingly, some data have also reported that activation of TIM-1 signaling by using TIM-4 fusion protein can lead to the cell apoptosis in colon cancer cells, suggesting a different role of TIM-1 in defining cell fate of cancer cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [20] have also reported that increased TIM-1 expression is found in human gastric cancer tissues compared with the normal gastric tissues at both the mRNA and protein levels, and high expression of TIM-1 can serve as a novel prognostic factor for gastric cancer. Moreover, urinary TIM-1 can also be found in patients with clear renal cell carcinoma, and its expression is significantly correlated with tumor characteristics [21].…”
Section: Introductionmentioning
confidence: 99%
“…Опыт использования KIM-1 как опухолеассоциированного маркера почечноклеточного рака В ряде исследований было показано, что при ПКР определенных гистологических типов уровни KIM-1 в моче и / или плазме крови (uKIM-1 и pKIM-1 соответственно) возрастают [15,16,[41][42][43]. Количество таких работ пока невелико, однако они обусловливают актуальность изучения маркера в аспекте активного выявления, уточняющей диагностики и мониторинга эффективности лечения больных с этим заболеванием.…”
unclassified
“…Подтверждение повышенной экспрессии uKIM-1 у больных ПКР продемонстрировано еще в одном исследовании, включившем 40 больных ПКР с планируемой нефрэктомией или резекцией почки, а также 30 здоровых добровольцев (контрольная группа) [42]. Уровень uKIM-1 также нормализовали по концентрации креатинина.…”
unclassified
See 1 more Smart Citation